Effect of indium addition on microstructure, wettability, shear strength and creep behavior of sn100c solder - Abdullah, Nabihah (2019)
Due to environmental concern of lead toxicity, the use of lead-free solder has been widely used in electronic packing industries. In finding alternative of lead-free solder to replace the current lead solder, the lead-free solder should have a melting point close to lead solder (183°C), has good wettability, as well as excellent physical and mechanical properties. Among lead-free solders, Sn-Cu alloy is the most compatible to replace the lead solder. However, Sn-Cu solder has a high melting point and wetting angle compared to lead solder. The high melting point caused high soldering temperature, which might expose the sensitive components and substrate to a risk since it cannot withstand high temperature. The aim of this project is to evaluate thermal behaviour, microstructure, wettability, mechanical properties and creep behaviour of SN100C solder (Sn-0.7Cu-0.05Ni-0.01Ge) with addition of indium. The microstructure characteristics, physical and mechanical properties, and creep behaviour of SN100C solder were investigated using optical microscope (OM), scanning electron microscope, differential scanning calorimetry (DSC), and Instron machine. With indium addition from 0wt% to 2.0wt%, the melting temperature was reduced from 229.64 °C to 225.40°C. The wettability of solder alloys improved with increasing amount of indium. Bulk microstructure of solder alloys showed that the grain size of solder decreased, and β-Sn grain became more refined with increasing amount of indium added. It is also observed that (Cu, Ni)6Sn5 and Sn-Cu-Ni-In IMC were formed with indium from 0.5 wt% to 2.0 wt.% alongside the Cu6Sn5. The addition of 2.0wt% of indium also led to an improvement of shear strength. In term of creep properties, the alloy with 2.0wt% indium gave the highest creep resistance due to the refinement of microstructure. The refinement and formation of IMCs in the solder alloys can result in impeding the dislocation movement. According to the obtained stress exponent and activation energies, it is proposed that the dominant deformation mechanism in In-added SN100C solder is dislocation climb over the temperature range investigated. The indium addition at 2.0wt% was observed to induce grain refinement of SN100C solder with higher mechanical properties, better wettability behaviour and improved creep resistance.